2011
DOI: 10.1177/0888406411401919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immediate Feedback Delivered via Webcam and Bug-in-Ear Technology on Preservice Teacher Performance

Abstract: University faculty and supervisors dedicated to the preparation of future teachers are facing more challenges than ever before in doing more with less. This includes supervising more preservice teachers in more schools, spread out over a wide geographic area. Feedback is essential to learning, and recent research suggests that the most effective feedback is immediate rather than delayed. New advances in technology may make the job of supervision more efficient and when used to provide immediate feedback, more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 17 publications
8
100
0
Order By: Relevance
“…Four articles from a behaviouristic point of view investigated feedback via bug-in-the-ear technology and its effects on (student) teachers' teaching behaviours (Goodman et al, 2008; Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002). All of them concluded that immediate feedback is effective, and, in addition, Goodman et al (2008) and Scheeler et al (2010) advised that feedback should be specific and corrective.…”
Section: Behaviourismmentioning
confidence: 99%
See 4 more Smart Citations
“…Four articles from a behaviouristic point of view investigated feedback via bug-in-the-ear technology and its effects on (student) teachers' teaching behaviours (Goodman et al, 2008; Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002). All of them concluded that immediate feedback is effective, and, in addition, Goodman et al (2008) and Scheeler et al (2010) advised that feedback should be specific and corrective.…”
Section: Behaviourismmentioning
confidence: 99%
“…As Table 3 shows, from a behaviouristic perspective (Goodman et al, 2008;Rodriguez et al, 2009;Scheeler et al, 2010Scheeler et al, , 2012Scheeler & Lee, 2002), feedback should be given immediately and/or timely (Auld et al, 2010). In addition, Van der Kleij et al (2012; from social constructivism) described that feedback can be provided immediate or delayed.…”
Section: Timingmentioning
confidence: 99%
See 3 more Smart Citations